Pengaruh Literasi Keuangan Dan Literasi Digital Terhadap Minat Penggunaan Digital Payment Pada Mahasiswa - Fatasya, Putri Aulia; Marandika, Muhammad Andrian; Azizah, Rahmi Nur; Purnamasari, Helen; Asnaini, Asnaini (Borneo Islamic Finance and Economics Journal, 2024)
Abstract This study aims to analyze the influence of financial literacy and canggih literacy on the interest in using canggih payments among students of the Faculty of Islamic Economics and Business (FEBI) UIN Fatmawati Sukarno Bengkulu. The method used in this study is a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 70 respondents from a population of 230 students. The results of the study indicate that financial literacy has a positive and significant influence on the interest in using canggih payments, with a regression coefficient of 0.271. In addition, canggih literacy has also been shown to contribute positively to the use of canggih payment methods, with a regression coefficient of 0.258. Thus, it can be concluded that financial literacy and digital literacy partially have a positive and significant effect on the use of advanced payment tools. These findings emphasize the importance of increasing financial and canggih literacy among students to encourage more active and wise use of canggih payments. This research is expected to be a reference for the development of educational programs that focus on financial literacy and digital payments in educational institutions. Thus, the results of this study can provide knowledge to policy makers in designing effective strategies to improve students' understanding of the benefits and risks of using advanced payments. Keywords: Financial literacy, canggih literacy, canggih payments.